Germinated brown rice relieves hyperlipidemia by alleviating gut microbiota dysbiosis - Chuan-ying REN; Shan ZHANG; Bin HONG; Li-jun GUAN; Wen-gong HUANG; Jun-ran FENG; Di-xin SHA; Di YUAN; Bo LI; Ni-na JI; Wei LIU; Shu-wen LU (Journal of Integrative Agriculture, 2023)
Hyperlipidemia is a frequent metabolic disorder that is closely associated with diet. It is believed that brown rice, containing the outer bran layer and germ, is beneficial for the remission of hyperlipidemia. This study established a rat model of hyperlipidemia by feeding a high-fat diet. The hypolipidemic potential of germinated brown rice (Gbrown) and germinated black rice (a germinated black-pigmented brown rice, Gblack) were explored in the model rats, mainly in the aspects of blood lipids, lipases, apolipoproteins, and inflammation. The gut microbiota in hyperlipidemic rats receiving diverse dietary interventions was determined by 16S rDNA sequencing. The results showed that the intervention of Gbrown/Gblack alleviated the hyperlipidemia in rats, evidenced by decreased TC, TG, LDL-C, and apolipoprotein B, and increased HDL-C, HL, LPL, LCAT, and apolipoprotein A1. Gbrown/Gblack also weakened the inflammation in hyperlipidemia rats, evidenced by decreased TNF-α, IL-6, and ET-1. In addition, 16S rDNA sequencing revealed that the diet of Gbrown/Gblack elevated the abundance and diversity of gut microbiota in hyperlipidemia rats. At the phylum level, Gbrown/Gblack decreased Firmicutes, increased Bacteroidetes, and decreased the F/B ratio in hyperlipidemia rats. At the genus level, Gbrown/Gblack decreased Streptococcus and increased Ruminococcus and Allobaculum in hyperlipidemia rats. Some differential microbial genera relating to lipid metabolism were also determined, such as the Lachnospira and Ruminococcus in the Gblack group, and the Phascolarctobacterium, Dorea, Turicibacter, and Escherichia-Shigella in the Gbrown group. Notably, the beneficial effect of Gblack was stronger than Gbrown. To sum up, the dietary interventions of Gbrown/Gblack contributed to the remission of hyperlipidemia by alleviating the dysbiosis of gut microbiota.